Dysbiosis and Metabolic Dysregulation of Salivary Microbiota in Schizophrenia - Wang J; Lu L; Ren L; Zhu R; Jiang Y; Qiao Y; Li Y (Journal of Multidisciplinary Healthcare)
Jie Wang,1,* Lin Lu,2,* Le Ren,1 Rui Zhu,2 Yao Jiang,2 Yanan Qiao,1 Yongming Li1 1Shanghai Engineering Research Center of Tooth Restoration and Regeneration & Tongji Research Institute of Stomatology & Department of Orthodontics, Shanghai Tongji Stomatological Hospital and Dental School, Tongji University, Shanghai, 200072, People’s Republic of China; 2Stomatology Hospital, School of Stomatology, Zhejiang University School of Medicine, Zhejiang Provincial Clinical Research Center for Oral Diseases, Key Laboratory of Oral Biomedical Research of Zhejiang Province, Cancer Center of Zhejiang University, Engineering Research Center of Oral Biomaterials and Devices of Zhejiang Province, Hangzhou, 310000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yongming Li, Email liyongming@tongji.edu.cn; Yanan Qiao, Email a513624@126.comBackground: Schizophrenia (SZ) is a chronic, severe mental disorder that presents significant challenges to diagnosis and effective treatment. Emerging evidence suggests that gut microbiota may play a role in the disease’s pathogenesis. However, fewer studies have directly investigated the potential links between oral microbiota and SZ.Purpose: This study aimed to explore the relationship between salivary microbiota dysbiosis and SZ, examining microbial and metabolic alterations that may contribute to SZ pathophysiology.Methods: Salivary samples from 30 hospitalized patients diagnosed with SZ and 10 healthy controls were collected. The microbial and metabolic profiles were analyzed using 16S rRNA gene sequencing and metabolomic profiling. Clinical parameters, including oral health status, were also evaluated to minimize variability in sampling.Results: Patients with SZ exhibited significantly poorer oral health compared to healthy controls, with more missing teeth and worse periodontal status. Microbiota sequencing revealed notable alterations in the overall structure and composition of the salivary microbiome in SZ patients, characterized by increased abundance of specific genera such as Neisseria and Porphyromonas. Metabolomic analysis indicated significant differences between the SZ and control groups, with upregulation of key metabolic pathways, including “β-alanine metabolism” and “vitamin digestion and absorption”. Correlations between microbial dysbiosis and elevated levels of certain metabolites, such as L-methionine sulfoxide (L-MetO) and tyramine, were observed, suggesting links to oxidative stress.Conclusion: The study highlights the presence of significant dysbiosis and metabolic dysfunction in the salivary microbiota of SZ patients, suggesting that alterations in the oral microbiome may contribute to SZ pathogenesis. These results provide new insights into potential diagnostic biomarkers and therapeutic targets for SZ. Further studies with larger sample sizes are required to validate these findings.Keywords: schizophrenia, oral microbiome, dysbiosis, 16S rRNA, salivary metabolome